2011
DOI: 10.1017/s0022149x11000721
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of enteric infections induced by the acanthocephalanProfilicollis chasmagnathiin Olrog's gull,Larus atlanticus, from Argentina

Abstract: Acanthocephalans can be pathogenic helminths of marine birds. Every year during the breeding season, there is variable mortality among prefledged chicks from the largest known Olrog's gull (Larus atlanticus) colony. Mortality has been associated with infection by the acanthocephalan Profilicollis chasmagnathi. Our aim was to study the role of chicks' size as a risk factor for intensity of infection and severe pathology, and to expand upon previous pathological findings reported in acanthocephalan-infected chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…The pathological findings presented here agree with other descriptions made in charadriiform birds, with necrotizing transmural lymphocytic and granulomatous inflammation, serositis and peritonitis (Taraschewski, 2000;La Sala et al, 2011;Fenton et al, 2018). Taraschewski (2000) observed that, the pathogenicity of acanthocephalans is mainly caused by: (1) density of worms and (2) depth of parasite penetration into the host tissues.…”
Section: Discussionsupporting
confidence: 91%
“…The pathological findings presented here agree with other descriptions made in charadriiform birds, with necrotizing transmural lymphocytic and granulomatous inflammation, serositis and peritonitis (Taraschewski, 2000;La Sala et al, 2011;Fenton et al, 2018). Taraschewski (2000) observed that, the pathogenicity of acanthocephalans is mainly caused by: (1) density of worms and (2) depth of parasite penetration into the host tissues.…”
Section: Discussionsupporting
confidence: 91%
“…Profilicollis chasmagnathi uses crabs from estuarine environments as intermediate hosts (Holcman-Spector et al ., 1977; Martorelli, 1989; La Sala et al ., 2012) and the gulls L. atlanticus and L. dominicanus as definitive hosts (e.g. Díaz et al ., 2011; La Sala et al ., 2013). Profilicollis altmani has the mole crab E. brasiliensis , which inhabits sandy beaches, as intermediate host.…”
Section: Resultsmentioning
confidence: 99%
“…This latter species has a large bi-oceanic distribution and has been recorded along the Pacific coast of North America (California) and South America (Chile) and along the Atlantic coast of North America (Rhode Island, North Carolina) and the Gulf of Mexico (Florida and Mississippi). Meanwhile, for the South American Atlantic coast the thorny-headed worm P. chasmagnathi has been cited with the crab species Neohelice granulata and Cyrtograpsus angulatus as intermediate hosts (Holcman-Spector et al ., 1977; Alda et al ., 2011; La Sala et al ., 2012) and Larus atlanticus and L. dominicanus as definitive hosts (Diaz et al , 2011; La Sala et al ., 2013). There is a mention of cystacanths of P. altmani infecting Emerita brasiliensis and Calidris canutus in Rio, southern Brazil (Buehler et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although the evolution of parasites and that of hosts are not independent of each other, parasites can evolve far more rapidly than hosts (Kochin et al ., 2010). As a consequence, parasites can switch hosts in a given environment (Kochin et al ., 2010), and a single parasite species can have multiple intermediate and definitive host species (Near, 2002; Mayer et al ., 2003; Royal et al ., 2004; La Sala & Martorelli, 2007; Steinauer et al ., 2007; Kochin et al ., 2010; La Sala et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%